Feasibility study of implementation of augmented reality in a telecommunications operator - Hayde, Cristian Tadeu Von Der; Tamborlin, Norberto; Souza, Ricardo Roncalho de; Dalfovo, Oscar (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Introduction: Augmented Reality (AR) is a new technology that allows companies to innovate in order to communicate. It is defined as the combination of the real world with virtual objects. Objective: To identify the feasibility of implementation of AR in a telecommunications company. Methodology: We used qualitative research, descriptive through documentary research of secondary data. Results: The investment for the use of AR only the store operator, where the research was performed, would not be profitable, given the size of the unit and the universe of consumers that would be achieved with the proposed deployment of AR. But the operator at Brazil level can make great advantage of AR in marketing. Conclusions: It was suggested the use of AR for Operator as a means of innovation and differential against competitors. The knowledge gained in this work was of great importance because it provide study AR, learn the concept, its benefits and the areas that can be used. Keywords: Augmented reality. Telecommunication. Information and communication technology. Link para o texto completo (PDF)http://www.uel.br/revistas/uel/index.php/informacao/article/view/13399/pdf_16